The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.7456/1060agse/046
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cognitive Behavioral Couple Therapy on Reduction of Marital Conflicts and Burnout of Couples

Abstract: Introduction and objective: family is the most important institute of every society and the society will be developed if the family positively does their performances. If there is a conflict in the family, its performance will be disordered. This study has been conducted to assess the effect of cognitive behavioral couple therapy on reduction of marital conflicts and burnout of couples. Methodology: the type of this experimental study is pretest-posttest with control and test groups. Statistical population of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Thus, this study was also positive because according spouses’ reports, they improved their perception of cognitive distortions and of their partners, and consequently, they also reported improvements in communication, dyadic adjustment, and depressive and anxiety symptoms. In this article, we have emphasized that CBCT intervention modified this panorama significantly; both spouses within a couple showed reduced depression levels, improved marital adjustment, and social skills in the post therapy, thereby corroborating the literature data (Cohen et al, 2014; Del Prette et al, 2008; Epstein & Zheng, 2017; Fischer et al, 2016; Moazinezhad & Arefi, 2017; Rajani et al, 2016; Sardinha et al, 2009; Shayan et al, 2018; Sher, 2011).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, this study was also positive because according spouses’ reports, they improved their perception of cognitive distortions and of their partners, and consequently, they also reported improvements in communication, dyadic adjustment, and depressive and anxiety symptoms. In this article, we have emphasized that CBCT intervention modified this panorama significantly; both spouses within a couple showed reduced depression levels, improved marital adjustment, and social skills in the post therapy, thereby corroborating the literature data (Cohen et al, 2014; Del Prette et al, 2008; Epstein & Zheng, 2017; Fischer et al, 2016; Moazinezhad & Arefi, 2017; Rajani et al, 2016; Sardinha et al, 2009; Shayan et al, 2018; Sher, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…In summary, CBCT treatments may improve relationship satisfaction and promote well-being and also reduce emotional and psychological violence (Hurless & Cottone, 2018). It is necessary to note that long-term intimate relationships in conflicts might lead to a range of harm psychosocial variables, aggressive behaviors, and greater risk and vulnerabilities for mental disease (Rajani et al, 2016). On the order hand, healthier people are more likely to remain in an intimate relationship and they tend to have more resources to solve problems.…”
Section: Cognitive Behavioral Couple Therapy (Cbct)mentioning
confidence: 99%
“…The results of the this study showed that the mean score of total marital burnout after the intervention was significantly difference between two groups and the rate of total marital burnout was significantly decreased in experimental group. The results of Rajani's study showed that the implementation of cognitive-behavioral couple therapy in the experimental group significantly reduced conflict and marital burnout among couples [2]. A study conducted by Sirin with the aim of investigating the effect of family education programs on the marital burnout among married women showed that the implementation of this intervention program significantly reduced marital burnout among married women in the experimental group compared to the control group [31].…”
Section: Discussionmentioning
confidence: 99%
“…The history of marriage can be traced back to the beginning of history. Throughout history, marriage has been one of the most exciting and stressful events in everyone's life [1,2]. The formation of a healthy marriage is one of the factors for the successful establishment of a family, which will undoubtedly have a positive impact on society [3].…”
Section: Introductionmentioning
confidence: 99%